Teaching medical ethics symposium. Medical ethics in Manchester. Issue 3 (September 1987) - Brazier, M; Dyson, A; Harris, J; Lobjoit, M
Abstract : Manchester's multi-disciplinary approach to medical ethics combines established methods and new initiatives. There is a longstanding Medical Group and also, plans are evolving for the inclusion of medical ethics teaching in the undergraduate curriculum, the start of an MA in Health Care Ethics in October 1987 and the establishment of the Centre for Social Ethics and Policy to act as a focus within the university for research and study in a wider context.